The correlation of linguistic historiography with linguistic theory as conceived of by Valerii Akulenko - Вакуленко, Сергій Валентинович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
R. Simone formulated in the mid-1970s an ambitious programme of integrating linguistic historiography with linguistic theory. V. Akulenko’s Breve introducción histórica a la lingüística (La Habana, 1979) largely shared the same conceptual bearings and, moreover, made some steps towards putting a similar programme into practice. Both scholars regarded the history of science as instrumental in attaining better methodological awareness and focussed just as much on cognitive procedures as on the succession of theoretical models in linguistics and on the results achieved by each of them.